2021
DOI: 10.3390/microorganisms9050951
|View full text |Cite
|
Sign up to set email alerts
|

First Report of blaNDM-1 Bearing IncX3 Plasmid in Clinically Isolated ST11 Klebsiella pneumoniae from Pakistan

Abstract: The New Delhi Metallo-β-lactamase (NDM) is among the most threatening forms of carbapenemases produced by K. pneumoniae, well-known to cause severe worldwide infections. The molecular epidemiology of blaNDM-1-harboring K. pneumoniae is not well elucidated in Pakistan. Herein, we aim to determine the antibiotics-resistance profile, genes type, molecular type, and plasmid analysis of 125 clinically isolated K. pneumoniae strains from urine samples during July 2018 to January 2019 in Pakistan. A total of 34 (27.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
5
15
0
Order By: Relevance
“…Plasmid incompatibility (Inc) groups IncC, IncHI, IncF, IncR, and IncX3 were identified among carbapenem-resistant K. pneumoniae isolates, where the plasmid IncF group was the most frequent type and included IncFIA(HI1), IncFIB(K), IncFIB(K) (pCAV1099-114), IncFIB(pQil), IncFIB(pKPHS1), IncFII, IncFII(K), and IncFII(pKP91). Several studies showed similar findings ( 8 , 14 , 40 , 41 ). Even if all strains described here carry multiple plasmids, not all bla NDM-1 genes could be unambiguously assigned to a particular plasmid.…”
Section: Discussionsupporting
confidence: 61%
“…Plasmid incompatibility (Inc) groups IncC, IncHI, IncF, IncR, and IncX3 were identified among carbapenem-resistant K. pneumoniae isolates, where the plasmid IncF group was the most frequent type and included IncFIA(HI1), IncFIB(K), IncFIB(K) (pCAV1099-114), IncFIB(pQil), IncFIB(pKPHS1), IncFII, IncFII(K), and IncFII(pKP91). Several studies showed similar findings ( 8 , 14 , 40 , 41 ). Even if all strains described here carry multiple plasmids, not all bla NDM-1 genes could be unambiguously assigned to a particular plasmid.…”
Section: Discussionsupporting
confidence: 61%
“…Reports of high levels of antibacterial resistance [ 4 7 ] from hospitals as well as the community [ 8 , 9 ] in Pakistan, the fifth most populous country globally [ 10 ], places an additional burden on an overstressed and under resourced health care system. Circulating mobile genetic elements in bacterial species [ 5 , 7 , 11 ] that can transfer multidrug resistance genes within and between species have also been reported. Further, the detection of extensively drug resistant (XDR) Salmonella Typhi from Hyderabad, Pakistan [ 12 ] reinforces concerns over the complex interaction between environment and anthropogenic activities in contributing towards emerging AMR.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, an outbreak was caused by a clonally related bla NDM7 -producing E. coli strain, transmitted between six patients and leading to their colonization. Most noteworthy in Case Study 3, however, is the clear evidence of HGT, which occurred in patient E. The rapid global spread of bla NDM in different bacterial species is extensively reported in the literature, because this gene is carried on a broad host range of conjugative plasmids [ 28 , 29 ]. Here, we discuss two cases of HGT occurring between distinct bacterial species that were very likely mediated by a plasmid: (1) bla NDM-7 was transferred between IncX3-carrying E. coli and K. aerogenes (Case 3) and (2) bla NDM-1 was transferred between K. oxytoca and E. cloacae (Case 2), both carrying IncX3.…”
Section: Discussionmentioning
confidence: 99%